2021
DOI: 10.1097/qad.0000000000002990
|View full text |Cite
|
Sign up to set email alerts
|

Persistently lower bone mass and bone turnover among South African children living with well controlled HIV

Abstract: Objective: We evaluated longitudinal trends and associations between bone mass, bone turnover and inflammatory markers among South African children living with HIV (CLHIV) and controls.Design: We previously reported decreased bone mass among CLHIV independent of marked inflammation and increased bone turnover. The goal of this study was to evaluate longitudinal changes in bone mass, bone turnover and inflammation over 2 years.Methods: Longitudinal analyses were conducted among 220 CLHIV and 220 controls. Anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 61 publications
0
16
1
Order By: Relevance
“…By contrast, our study that was cited by Shen et al [1] showed that adolescents with detectable viral load had significantly lower IL-6 levels than controls, and those with an undetectable viral load had IL-6 levels comparable with controls [3].…”
contrasting
confidence: 89%
See 3 more Smart Citations
“…By contrast, our study that was cited by Shen et al [1] showed that adolescents with detectable viral load had significantly lower IL-6 levels than controls, and those with an undetectable viral load had IL-6 levels comparable with controls [3].…”
contrasting
confidence: 89%
“…Those seemingly opposite results may be because of the conditions under which cytokines were measured: whereas Shen et al [1] and Shiau et al [2] assessed plasma cytokines ex vivo, we measured the same cytokines after in-vitro stimulation of peripheral blood cells with phytohemagglutinin (PHA) [3].…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Munhoz and Moraes-Pinto [1] proposed an explanation of the discordant results between studies by Munhoz et al [3] and ourselves [2] with respect to measures of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha) among adolescents and children living with HIV and HIV-uninfected controls. Munhoz et al [3] using in-vitro stimulation of peripheral blood cells with phytohemagglutinin (PHA) reported that adolescents with detectable viral load had significantly lower IL-6 and comparable TNF-alpha levels than controls, and those with an undetectable viral load had IL-6 and TNF-alpha levels comparable with controls.…”
Section: Cytokines In Hiv Infection: Authors’ Replymentioning
confidence: 99%